2021
DOI: 10.21608/ejar.2021.50952.1044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intercropping systems of sesame with tomatoes under different intercropping dates of sesame on productivity of both crops. 1

Abstract: Field experiment was conducted at Sids Horticulture Research Station, in Beni-Suif Governorate in 2018 and 2019 summer seasons to study the effect of intercropping sesame (Shandaweel-3) with hybrid tomato (Nema 1400) in three intercropping patterns 100% tomato + (50%, 33% and 25% sesame) in addition solid planting of both crops under three sowing dates for sesame was also studied the effect on plant growth, yield attributes and yield of both crops. The experiment was implemented in a split plots design with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…However, the yield per unit area increased due to the efficient utilization of growth factors. Maximum yield per unit area can be obtained when individual plants are subjected to severe competition (Lamlom and Ahmed 2021). Sadeghi et al (2009) reported that basil is sensitive to plant density and lower densities do not produce sufficient fresh herbal yield per unit area.…”
Section: Fresh Herbal Yield Per Plantmentioning
confidence: 99%
“…However, the yield per unit area increased due to the efficient utilization of growth factors. Maximum yield per unit area can be obtained when individual plants are subjected to severe competition (Lamlom and Ahmed 2021). Sadeghi et al (2009) reported that basil is sensitive to plant density and lower densities do not produce sufficient fresh herbal yield per unit area.…”
Section: Fresh Herbal Yield Per Plantmentioning
confidence: 99%